2020
DOI: 10.1111/ene.14541
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological deterioration following thrombolysis for minor stroke with isolated internal carotid artery occlusion

Abstract: Background and purposeBetter understanding the incidence, predictors and mechanisms of early neurological deterioration (END) following intravenous thrombolysis (IVT) for acute stroke with mild symptoms and isolated internal carotid artery occlusion (iICAo) may inform therapeutic decisions.MethodsFrom a multicenter retrospective database, we extracted all patients with both National Institutes of Health Stroke Scale (NIHSS) score <6 and iICAo (i.e. not involving the Willis circle) on admission imaging, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…PLR had a specificity of 73.0% and a sensitivity of 56.4% for predicting END. For END was a composite outcome that includes initial NIHSS, it was speculated he NIHSS was associated with END, and we did obtain that NIHSS was independently related to END at admission, which was consistent with the conclusion of Boulenoir et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…PLR had a specificity of 73.0% and a sensitivity of 56.4% for predicting END. For END was a composite outcome that includes initial NIHSS, it was speculated he NIHSS was associated with END, and we did obtain that NIHSS was independently related to END at admission, which was consistent with the conclusion of Boulenoir et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the prevalence of post-thrombolysis END and post-thrombolysis ENI were 18.2% as well as 37.5%, respectively. These prevalence are in line with the previous researches [25][26][27][28][29]. In this observational study, we found NLR as well as PLR were associated with post-thrombolysis END.…”
Section: Discussionsupporting
confidence: 92%
“…In case of disagreement about the NIHSS score evaluation, a third neurologist in this center was invited for a nal decision. Post-thrombolysis END was de ned as an increase in the NIHSS score by ≥ 4 points in the total score within 24 hours after thrombolysis [7,24,25].Meanwhile, post-thrombolysis ENI was de ned as a decrease in the NIHSS score by ≥ 4 points in the total score or a complete resolution of neurological de cits within 24 hours after thrombolysis [26][27][28].…”
Section: De Nition Of Post-thrombolysis Early Neurological Deterioratmentioning
confidence: 99%
“…Although we did not assess this association further, existing results have shown that thrombolysis may be associated with potential harm in patients presenting with an NIHSS score of 0-1 compared to patients with a score of 2-5 (21). Other results suggested that intravenous thrombolysis might also be associated with deterioration due to thrombus fragmentation in some patients with ICA occlusion (22). The efficacy of bridging thrombolysis in those patients also remains to be elucidated (23).…”
Section: Discussionmentioning
confidence: 89%